(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
The article theoretically substantiates, develops, and experimentally verifies the effectiveness of an authorial program for implementing game-based technologies in physical education lessons for younger school-age children to enhance attention properties. Under experimental conditions, positive changes were observed in the dynamics of the experimental group of younger schoolchildren regarding attention properties, particularly productivity, stability, span, concentration, and shifting. The research aim is to determine the effectiveness of implementing game-based technologies in the physical education process of younger school-age children. Organization and Methods. The study examined the level of attention properties, including productivity, stability, span, concentration, shifting, and experimentally verified the effectiveness of a program integrating game-based technologies into the physical education process of younger school-age children. A total of 47 schoolchildren participated in the study (24 girls and 23 boys). Research methods included literature analysis, psychodiagnostic methods (Tests Landolt rings), pedagogical experiment, and mathematical statistics. Results. A program for implementing game-based technologies in physical education lessons for younger school-age children was presented and scientifically substantiated. The program included the application of game-based technologies in physical education through a comprehensive combination of sports and movement games, entertainment activities, digital multimedia applications (such as BetterMe, Active Arcade), storyline scenarios, game creativity, play-based gymnastics, and relaxation exercises aimed at developing students' attention. Conclusions. The developed program was implemented in the educational process, and its effectiveness was confirmed. The research results demonstrated its positive impact on attention properties, particularly productivity, stability, span, concentration, and shifting in younger school-age children, as confirmed by mathematical statistics.